2021
DOI: 10.1016/j.ssmph.2021.100888
|View full text |Cite
|
Sign up to set email alerts
|

Are children in female-headed households at a disadvantage? An analysis of immunization coverage and stunting prevalence: in 95 low- and middle-income countries

Abstract: Studies of inequalities in child health have given limited attention to household structure and headship. The few existing reports on child outcomes in male and female-headed households have produced inconsistent results. The aim of our analyses was to provide a global view of the influence of sex of the household head on child health in cross-sectional surveys from up to 95 LMICs. Studied outcomes were full immunization coverage in children aged 12–23 months and stunting prevalence in under-five children. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
1
14
2
Order By: Relevance
“…Household headship characteristics of gender and education were essential factors for stunting. This result differs from a prior study that showed that even after adjusting for family wealth, education, and residence, there were no changes in stunting prevalence based on household headship [ 45 ]. Most female-headed households regard themselves as vulnerable and less stable livelihoods [ 46 ] because of their often lower earnings and restricted access to vital services [ 45 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Household headship characteristics of gender and education were essential factors for stunting. This result differs from a prior study that showed that even after adjusting for family wealth, education, and residence, there were no changes in stunting prevalence based on household headship [ 45 ]. Most female-headed households regard themselves as vulnerable and less stable livelihoods [ 46 ] because of their often lower earnings and restricted access to vital services [ 45 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Although studies assessing the relationship between FHH and birth registration are scarce, other studies exploring associations with child health and nutrition outcomes also showed high variability in the results [ 4 , 22 , 31 ]. There are at least two main explanations for the lack of consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of some subgroups were small in many countries, and our final typology was restricted to three categories: (a) male-headed household (MHH); (b) FHH with any adult male; (c) FHH without a male. This typology is described in detail in a previous publication [ 12 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 Nevertheless, some studies were unable to verify this association. 37 Our results of an interaction between female head of household and other modifiable factors might be an indicator for researchers and policymakers to explore women empowerment in practice.…”
Section: Discussionmentioning
confidence: 88%